The cook and the gardener : recipes and writings from France - Hesser, Amanda (W. W. Norton & Company, 2025)
"A 25th anniversary edition of seasonal recipes from a traditional French garden. The ancient link between the gardener and the cook is at the heart of this remarkably evocative cookbook, in which Amanda Hesser tells the story of a year she spent as a cook in a seventeenth-century château in Burgundy. The property's old gardener was wary of her at first, but over time they became friends, and he showed her a way of life that was quickly disappearing from France. With more than 240 recipes, organized by season, Hesser's book puts the garden's harvest at the center of cooking. In spring and summer, it's carrots with tarragon and braised lamb with peas. Summer chapters feature zucchini-lemon soup and raspberries eau-de-vie, as well as extensive advice on canning fresh summer produce so it can be enjoyed during the colder months. Fall and winter inspire cozier dishes, including a warm escarole salad and Brussels sprouts with brown butter. Hesser's innovative and delicious farm-to-table approach transforms everyday ingredients into extraordinary meals. These recipes are simple yet sublime, with accessible ingredients and vivid, helpful instructions. By bringing the kitchen closer to the garden, The Cook and the Gardener gives home cooks a new understanding of how to make meals from seasonal produce, whether it comes from the supermarket, the farmers market, or their own gardens." --